PENGARUH SUSTAINABILITY REPORT, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Andriansyah, (2021)
This study aims to determine the effect of sustainability report, profitability, and leverage on firm value in energy and basic materials sector companies listed on the Indonesia Stock Exchange for the period 2015-2019. This research is a quantitative research and uses secondary data in the form of the company's annual report. This study used a sample of 70 companies in the energy and basic materials sector. This study analyzed the data through regression model selection test, classic assumption test, panel data regression, and hypothesis testing simultaneously (f test) and partial (t test). The results of this study showed that: (1) sustainability report has no significant effect on firm value, (2) profitability has a significant negative effect on firm value, and (3) leverage has a significant negative effect on firm value.